اللغة بين وضع الرمز و أداء الدلالة - وقاف، حسين بن حبيب (جامعة البعث, 2013)
يحاول هذا البحث أن يتناول اللغة في سيرورة تكاملها منذ نشأة الرمز اللغوي، وحتى دخولها ساحة الاستثمار التواصلي، وأداءها لوظيفتها كسلعة تعبيرية، ومنظومة قيم معنوية، تقوم بجملة من المهام المنوطة بها، على مستويات مختلفة، كما يحاول أن يلقي الضوء على الجانب الاقتصادي الاستثماري للغة، وما يرتبط به من مفاهيم اقتصادية، يمكن النظر من خلالها إلى اللغة من زاوية مختلفة، تبرز خصائصها التداولية، وتبين النواميس المترتبة على التعامل معها كذات اعتبارية، تتجاذبها قواعد الاستخدام الحسي، ونواميس الأحكام العقلية والاجتماعية. This study is trying to discuss language and its integration from bigning of lingual symbol until goinjinto field of communicative investment and per forminjits function as an expressive commodity and system of mor al values which carryout some functionsassociuted with that sistem on different levels. On theother hand, this study is yrying to hilijh t the investment al economical side of language and the economical concepts linked to that side. \ From these concepts we can see language from several sides which bring out the sirculative characteristics of language and clarify the laws resulting from dealing withit and show the rules of sensual use and laws of socialand men taljudgments which over lap with.
Keywords: اللغة العربية -- الرمز -- الدلالة اللغوية -- الاقتصاد اللغوي